RBC MAGNESIUM & PLASMA MAGNESIUM IN PRECLAMPSIA & NORMAL PREGNANCY - DR. RAMA SHOURI MD,; DR. P. KIRANMAI MD,; DR. J. RAMA RAO MD, (International Journal of Pharma and Bio Sciences, 2015)
Preeclampsia is pregnancy specific, multisystem disorder of unknown etiology occurring in 6.8% of all the pregnancies.Together with other hypertensive disorders of pregnancy,it is the 3rd most common cause of maternal mortality. Due to significant role of Magnesium in physiological regulation of blood pressure. For early diagnosis of preeclampsia, this study is conducted to measure the Mg levels in preeclampsia and normal pregnant women of same gestational age. Mg in both plasma and erythrocytes were estimated in 30 normal pregnant women and 100 preeclampsia pts between 24-34 wks of gestation.The data is analyzed with Prism statistics. In this study there is a significant decrease in RBC Mg and Plasma Mg in preeclampsia pts compared to normal pregnant women (p<0.05).In preeclampsia pts Plasma Mg is 1.44mg/dl, RBC Mg is 5.215mg/dl with the cut off value being 1.763mg/dl for Plasma Mg and 6.36mg/dl RBC Mg. The sensitivity of RBC Mg is 99% and specificity is 96.6%with diagnostic efficiency of 98% with regards to preeclampsia. RBC Mg is a more useful screening test to predict Pregnancy induced Hypertension in pregnant women.